Determinants of investment expenditure of local government (voivodeships) - Zawora, Jolanta (Uwarunkowania wydatków inwestycyjnych samorządów województw, 2019)
Investments of the local government are an important determinant of development both for the regions and for the whole society. The aim of the article is to evaluate the possibility of financing investment activities by the local governments at voivodeship level in Poland. The scope of investment expenditures of these units was also analysed. The adopted time scope of the study covers the period 2012-2018. Among the levels of the local government units, voivodeship allocated the largest part of funds for investment. The level of investment expenditure of local governments varied greatly from region to region
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 154-167
Keywords: investment expenditures; financial determinants; voivodeship local governments; wydatki inwestycyjne; determinanty finansowe; samorządy województw